Understanding Cr(III) Action on Mitochondrial ATP Synthase and AMPK Efficacy: Insights from Previous Studies-a Review - Gencoglu, Hasan; Orhan, Cemal; Şahin, Kazım (Springernature, 2024)
Chromium supplementation has been notably recognized for its potential health benefits, especially in enhancing insulin sensitivity and managing glucose metabolism. However, recent studies have begun to shed light on additional mechanisms of action for chromium, expanding our understanding beyond its classical effects on the insulin-signaling pathway. The beta subunit of mitochondrial ATP synthase is considered a novel site for Cr(III) action, influencing physiological effects apart from insulin signaling. The physiological effects of chromium supplementation have been extensively studied, particularly in its role in anti-oxidative efficacy and glucose metabolism. However, recent advancements have prompted a re-evaluation of chromium's mechanisms of action beyond the insulin signaling pathway. The discovery of the beta subunit of mitochondrial ATP synthase as a potential target for chromium action is discussed, emphasizing its crucial role in cellular energy production and metabolic regulation. A meticulous analysis of relevant studies that were earlier carried out could shed light on the relationship between chromium supplementation and mitochondrial ATP synthase. This review categorizes studies based on their primary investigations, encompassing areas such as muscle protein synthesis, glucose and lipid metabolism, and antioxidant properties. Findings from these studies are scrutinized to distinguish patterns aligning with the new hypothesis. Central to this exploration is the presentation of studies highlighting the physiological effects of chromium that extend beyond the insulin signaling pathway. Evaluating the various independent mechanisms of action that chromium impacts cellular energy metabolism and overall metabolic balance has become more important. In conclusion, this review is a paradigm shift in understanding chromium supplementation, paving the way for future investigations that leverage the intricate interplay between chromium and mitochondrial ATP synthase.
Keywords: Cr(III) action; Metabolic regulation; Glucose metabolism; Energy homeostasis; Nutrient transporters